The paradox of being : truth, identity, and images in Daoism - Andersen, Poul, 1944- (Cambridge, Massachusetts : Harvard University Asia Center, 2019)
"Addresses the concept of truth in Chinese Daoist philosophy and ritual. Through wide-ranging research into Daoist ritual, both in history and as it survives in the present day, shows that the concept of true reality that informs this tradition posits being as a paradox anchored in the inexistent Way"--Provided by publisher.
Copyright Page / Author: Poul Andersen -- Dedication / Author: Poul Andersen -- Illustrations / Author: Poul Andersen -- Acknowledgments / Author: Poul Andersen -- Note to the Reader / Author: Poul Andersen -- Introduction / Author: Poul Andersen -- Chapter 1 Truth and Subjectivation / Author: Poul Andersen -- Chapter 2 Truth and Knowledge / Author: Poul Andersen -- Chapter 3 The Concept of "Zhen" / Author: Poul Andersen -- Chapter 4 Liturgical Symbols and Images / Author: Poul Andersen -- Chapter 5 Unity and Identity / Author: Poul Andersen -- Chapter 6 Sincerity and Ascent to Heaven / Author: Poul Andersen -- Closing Remarks / Author: Poul Andersen.
Includes bibliographical references and index.
JSTOR
Keywords: Taoism; Truth -- Religious aspects -- Taoism; Taoism -- Rituals; Taoist philosophy; Taoïsme.; Philosophie taoïste.; Taoism; Taoism; Taoism -- Rituals; Taoist philosophy